Closure of Alveolar Cleft by Iliac Bone Grafting: a Case Report - A S M Ariful Islam; Nafisa Afroze; Md Shofikul Islam; Jeyasmin Akter Lipi; Najiur Rahman Bikram; Fatamatuj Jahura Shuha (Update Dental College, 2023)
Introduction: Orofacial clefts are the most common craniofacial birth defects, affecting a significant number of individuals worldwide. The alveolar cleft is a developmental defect that affects the alveolar process of the maxilla and is often associated with cleft lip and palate. Methods: In this case report, we present the case of a 20-year-old female patient with alveolar cleft who underwent secondary alveolar cleft reconstruction using autologous iliac bone grafting. The aim of the procedure was to restore the function and form of the maxillary arch, facilitate ridge augmentation for further prosthetic rehabilitation, repair the nasal floor, and facilitate orthodontic treatment. Results: The procedure was successful in achieving the desired outcomes, and the patient's occlusal relationship was improved. Additionally, the alar base symmetry was enhanced, and speech was improved. Conclusion: Alveolar cleft reconstruction using autologous iliac bone grafting is a successful approach to treating alveolar clefts. The procedure can restore the form and function of the maxillary arch and facilitate further prosthetic rehabilitation and orthodontic treatment. The effectiveness of the procedure should be monitored closely to ensure optimal outcomes. Update Dent. Coll. j: 2023; 13(1): 35-39